A review: nutrition and process attributes of corn in pet foods. Issue 31 (1st November 2022) - Corsato Alvarenga, Isabella; Dainton, Amanda N.; Aldrich, Charles G.
Abstract: Corn is one of the largest cereal crops worldwide and plays an important role in the U.S. economy. The pet food market is growing every year, and although corn is well utilized by dogs, some marketing claims have attributed a negative image to this cereal. Thus, the objective of this work was to review the literature regarding corn and its co-products, as well as describe the processing of these ingredients as they pertain to pet foods. Corn is well digested by both dogs and cats and provides nutrients. The processing of corn generates co-products such as corn gluten meal and distillers dried grains with solubles that retain quality protein, and fibrous components that dilute dietary energy. Further, corn has much functionality in extrusion processing. It may yield resistant starch under certain processing conditions, promoting colonic health. Carotenoids in corn may enhance immune support in companion animals if concentrated. Mycotoxin contamination in grains represent a health hazard but are well controlled by safety measures. Genetically modified (GM) corn is still controversial regarding its long-term potential for mutagenicity or carcinogenicity, thus more long-term studies are needed. In conclusion, the negative perception by some in the pet food market may not be warranted in pet foods using corn and its co-products.